The Pacific Festivals of Aotearoa New Zealand : Negotiating Place and Identity in a New Homeland - Mackley-Crump, Jared (Book collections on Project MUSE., 2015)
With a history now stretching back four decades, Pacific festivals of Aotearoa assert a multicultural identity of New Zealand and situate the country squarely within a sea of islands. In this volume, Jared Mackley-Crump gives a provocative look at the changing demographics and cultural landscape of a place frequently viewed through a bicultural lens, Pākehā and Māori. Taking the post-World War II migrations of Pacific peoples to New Zealand as its starting point, the story begins in 1972 with the inaugural Polynesian Festival, an event that was primarily designed as a Māori festival, now known as Te Matatini, the largest Māori performing arts event in the world. Two major moments of festivalization are considered: the birth of Polyfest in 1976 and the inaugural Pasifika Festival of 1993. Both began in Auckland, the home of the largest Pacific communities in New Zealand, and both have spawned a series of events that follow the models they successfully established. While Polyfests focus primarily on the transmission of performance traditions from culture bearers to the young, largely New Zealand-born generations, Pasifika festivals are highly public community events, in which diverse displays of material culture are offered up for consumption by both cultural tourists and Pacific communities alike. Both models have experienced a significant period of growth since 1993, and here, the author presents a thought-provoking and wide-ranging analysis to explain the phenomenon that has been called a "Pacific renaissance." Written from an ethnomusicological perspective, The Pacific Festivals of Aotearoa New Zealand incorporates lively first-person observations as well as interviews with festival organizers, performers, and other important historical figures. The second half of the book delves into the festival space, uncovering new meanings about the function and role of music performance and public festivity. The author skillfully challenges accounts that label festivals as inauthentic recreations of culture for tourist audiences and gives both observers and participants an uplifting new approach to understand these events as meaningful and symbolic extensions of the ways diasporic Pacific communities operate in New Zealand.